2021
DOI: 10.1038/s41416-021-01614-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk-stratification of HPV-positive women with low-grade cytology by FAM19A4/miR124-2 methylation and HPV genotyping

Abstract: Background The introduction of primary HPV screening has doubled the number of colposcopy referrals because of the direct referral of HPV-positive women with a borderline or mild dyskaryosis (BMD) cytology (ASC-US/LSIL) triage test. Further risk-stratification is warranted to improve the efficiency of HPV-based screening. Methods This study evaluated the discriminative power of FAM19A4/miR124-2 methylation, HPV16/18 genotyping and HPV16/18/31/33/45 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“… 35 - 37 A recent post hoc analysis of two Dutch screening trials showed that HPV-positive women with ASC-US/LSIL and a negative methylation test have a CIN3+ risk of only 9.8% compared with a CIN3+ risk of 33.1% in women with ASC-US/LSIL and a positive methylation test. 38 Our current study showed that even when CIN2/3 is detected in methylation-negative women with ASC-US/LSIL, the probability of regression is nearly 90%. Together, these results support the implementation of methylation in cervical screening, possibly in combination with HPV16 genotyping, to triage HPV-positive women with ASC-US/LSIL for colposcopy.…”
Section: Discussionmentioning
confidence: 46%
“… 35 - 37 A recent post hoc analysis of two Dutch screening trials showed that HPV-positive women with ASC-US/LSIL and a negative methylation test have a CIN3+ risk of only 9.8% compared with a CIN3+ risk of 33.1% in women with ASC-US/LSIL and a positive methylation test. 38 Our current study showed that even when CIN2/3 is detected in methylation-negative women with ASC-US/LSIL, the probability of regression is nearly 90%. Together, these results support the implementation of methylation in cervical screening, possibly in combination with HPV16 genotyping, to triage HPV-positive women with ASC-US/LSIL for colposcopy.…”
Section: Discussionmentioning
confidence: 46%
“…Retrospective longitudinal screening studies showed that HPV‐positive but FAM19A4/miR124‐2 methylation‐negative women had a 14‐year CIN3+ risk equal to that of negative cytology triage outcome, and notably they had a lower risk for cervical cancer 16,55–57 . Recent data show that additional risk‐stratification of HPV‐positive women with low‐grade cytological abnormalities by FAM19A4/miR124‐2 methylation could substantially reduce direct colposcopy referral rate, while retaining high CIN3+ sensitivity 58 . Altogether, these findings support the use of cellular methylation markers as an interesting new molecular means for future cervical cancer screening, and the need to evaluate their performance in cohorts of vaccinated women.…”
Section: Methylation Of Cellular Genes and Risk Of Cervical Neoplasia...mentioning
confidence: 99%
“…Various candidate genes, targeting either host or HPV viral genomes, were studied in recent years as the targets of methylation sites [13][14][15][16] , resulting in signi cant heterogeneity between studies. Among these, a combination of methylation panels targeting the human gene EPB41L3 and the most carcinogenic HPV types-HPV16/18/31/33 (named S5 classi er) was one of the most studied methylation tests among different populations, such as among cancer patients [17] , HPV positive women with mild cytology abnormalities [18,19] , colposcopy referral population due to HPV16/18 + and/or cytology abnormalities [20] , or selected hrHPV + women derived from a population-based screening program [21,22] , even in HIV women [23] . All mentioned studies exhibited the desirable accuracy and feasibility of S5 classi er test, while population-based prospective studies are still lacking.…”
Section: Discussionmentioning
confidence: 99%